ASUHAN KEPERAWATAN PADA PASIEN DENGAN STROKE DI KAMPUNG PESING POGLAR, KELURAHAN KEDAUNG KALI ANGKE, KOTA JAKARTA BARAT, DKI JAKARTA - Wijianti Tri Lestari (2023)
Disturbances in the circulation of blood in the brain in English are also known as strokes. Based on data obtained from around the world, stroke is the most common cause of death in society with a probability of dying of (30%) to (35%), as well as the main cause of disability (World Health Organization, 2020). The results of research from Basic Health Research (Riskesdas, 2018), prove nationally that the number of stroke events in Indonesia in 2018 was (10.9%) or as many as 2,120,362 people. After carrying out this nursing care, it is hoped that the writer will be able to increase his knowledge and ability in providing nursing care to patients with strokes in Pesing Poglar Village, Kedaung Kali Angke Ward, West Jakarta City, DKI Jakarta. The research design used by researchers is a case study. The nursing diagnoses found in patients are impaired physical mobility associated with decreased muscle strength, ineffective peripheral perfusion associated with increased blood pressure, and ineffective health maintenance associated with inability to make proper judgments. While the interventions carried out were joint strengthening techniques (Range Of Motion), monitoring of vital signs and health education about stroke. From the cases found in patients, it was found that there was a difference between theory and cases during implementation in the field.